2016
DOI: 10.1080/10790268.2016.1180099
|View full text |Cite
|
Sign up to set email alerts
|

Association between presence of pneumonia and pressure ulcer formation following traumatic spinal cord injury

Abstract: A higher presence of pressure ulcers was found in individuals with pneumonia, after adjusting for injury severity, age, sex, and utilization of mechanical ventilation. Impaired inflammatory response and decreased mobility in individuals with pneumonia may predispose these individuals to develop pressure ulcers. Surveillance and preventive measures for pressure ulcers should be rigorous in individuals with SCI and pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
8

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
0
14
0
8
Order By: Relevance
“…13,24,27,43 A previous study also revealed association between pneumonia, mechanical ventilation and pressure ulcer. 44 The pathogenesis between the formation of pressure ulcers and presence of pneumonia may be related to an inflammatory response. 45 Demographics, such as age and gender, were not significant predictors of pressure ulcer formation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13,24,27,43 A previous study also revealed association between pneumonia, mechanical ventilation and pressure ulcer. 44 The pathogenesis between the formation of pressure ulcers and presence of pneumonia may be related to an inflammatory response. 45 Demographics, such as age and gender, were not significant predictors of pressure ulcer formation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos selecionados para esta revisão integrativa da literatura foram publicados em inglês e realizados nos seguintes países: um nos Países Baixos (15) , três nos Estados Unidos da América (EUA) (16)(17)(18) , um no Japão (19) e um na França (20) . O tamanho da amostra dos estudos variou entre 61 e 4.866 indivíduos adultos, predominantemente do sexo masculino e com lesão medular de etiologia traumática.…”
Section: Resultsunclassified
“…ção neurológica (15)(16)(17)(18) e dois estudos (19)(20) analisaram o risco após a reabilitação neurológica.…”
Section: Resultsunclassified
“…A total of 24 studies with 600,078 study participants were included to estimate the pooled prevalence of PU among SCI patients. In this meta-analysis, various countries were represented across a globe: 8 of studies were from America [6,[38][39][40][41][42][43], 7 from Europe [18,23,[44][45][46][47][48], 5 from Asia [20,28,[49][50][51], and 4 from Africa [7,22,24,52]. The highest prevalence of PU (56%) was reported from Europe [44], whereas the lowest prevalence (11%) was reported in a study conducted in America [6].…”
Section: Baseline Characteristic Of the Included Studiesmentioning
confidence: 99%